Economic integration in Central Asia regional economic cooperation member countries: Financing economic corridors and sovereign bonds market - Muhammad Ayub Mehar Khan (Asian Development Bank Institute (ADBI), 2020)
The nexus of the modes of financing, trade, and transport-related infrastructure, quantum of trade activities, and economic growth is the core area of this paper. It covers the impacts of regional economic integration of Central Asia Regional Economic Cooperation (CAREC) member countries on their trade and GDP growth. Though several bilateral and multilateral agreements to boost mutual trade are considered as a measure of economic integration, in the absence of high-quality physical infrastructure of transport and logistic services the implementation of such agreements is not possible. So, the provision of good trade and transport-related logistic services has been taken as a key indicator of integration among the countries in the region. The role of the magnitudes and modes of financing in determining the provision of logistic services and transport-related infrastructure has also been covered in the study. The results emphasize the causal relations between trade and transport-related infrastructure and GDP growth. The most important conclusion is the identification of short-term external borrowing as the most effective mode of financing. The study does not recommend long-term external borrowing or multilateral borrowing for the development of trade and transport-related infrastructure. The strong, significant, and robust impact of the share of short-term borrowing in total external debt on GDP growth, exports, and infrastructure development indicates the pressure on policy makers and economic managers to utilize resources effectively and efficiently. The global financial architecture should focus on the provision of short-term lending facilities to improve the efficiency of developing projects.
Keywords: F15; F34; R42; 330; Central Asia Regional Economic Cooperation; CAREC; regional integration; transport infrastructure; short-term external debt; domestic credit to private sector